2021
DOI: 10.3390/ma14206083
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Matrix Composites with Weak Particle Matrix Interfaces: Effective Elastic Properties Investigated Using Micromechanical Modeling

Abstract: The impact of weak particle-matrix interfaces in aluminum matrix composites (AMCs) on effective elastic properties was studied using micromechanical finite-element analysis. Both simplified unit cell representations (i.e., representative area or volume elements) and “real” microstructure-based unit cells were considered. It is demonstrated that a 2D unit cell representation provides accurate effective properties only for strong particle-matrix bond conditions, and underpredicts the effective properties (compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…The elastic constants for the different Al-TiB 2 compositions determined in 18 and used in the computational analysis are given in Table 1.…”
Section: Computational Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The elastic constants for the different Al-TiB 2 compositions determined in 18 and used in the computational analysis are given in Table 1.…”
Section: Computational Modelsmentioning
confidence: 99%
“…It is assumed that a continuum approach for modelling the composite represents well the constitutive response, as the cross-section of the material contains a large number of grains, as can be seen for all representative volume fractions in Figure 2. The authors previously identified the effective elastic parameters in 18 and the effective flow stresses are based on the values reported by the authors in. 13 However, the current batch of specimens was manufactured with some differences in the SPS parameters with respect to.…”
Section: Computational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from experimental and theoretical analytical methods, the microstructure-based representative volume element (RVE) has also been increasingly adopted to study double-phase composites [ 15 , 16 , 17 ]. Wang et al [ 16 ] proposed a 2D RVE of SiC/Al and studied its mechanical behavior by introducing the discrete distribution function of reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Для такой среды строится система определяющих соотношений с учетом условий для напряжений и деформаций на внутренних границах раздела (интерфейсах). В общем случае такая система уравнений решается численно, а усреднение получаемых результатов для представительных мезообъемов позволяет оценивать эффективные свойства композита [7][8][9][10][11][12][13]. Несмотря на хорошо известные преимущества (возможность явного учета микроструктуры и особых свойств интерфейсов), непосредственная компьютерная гомогенизация является вычислительно крайне затратной процедурой вследствие необходимости проведения многопараметрического исследования для определения однозначного соответствия внутренней структуры и макроскопических свойств материала.…”
Section: Introductionunclassified